2009
DOI: 10.1039/b803595d
|View full text |Cite
|
Sign up to set email alerts
|

Textural guidance cues for controlling process outgrowth of mammalian neurons

Abstract: We explore textural cues as a mechanism for controlling neuronal process outgrowth in primary cultures of mammalian neurons. The work uses a form of decal transfer lithography to generate arrays of PDMS posts of various dimensions and spacings on glass substrates that are rendered growth-compliant by subsequent treatment with a protein activator. Hippocampal neurons plated on these substrates are used to determine how the posts direct process growth by acting as attachment points or guidance cues. Textural fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 53 publications
(126 reference statements)
5
81
0
Order By: Relevance
“…The responses of nerve cells to surface roughness have been studied on various substrates, such as porous silicon, [3] thin titanium nitride films, [4] carbon nanotubes, [5] topographically molded poly(dimethylsiloxane), [6,7] silicon pillar arrays, [8] gallium phosphide nanowires, [9] aligned nanofiber arrays, [10] and silicon nanowires. [11] Previous studies showed that nerve cells exhibit enhanced attachment and viability [3][4][5][6] as well as the axonal guidance effect [7-10, 12, 13] on rough surfaces, as opposed to topographically flat surfaces.…”
mentioning
confidence: 99%
“…The responses of nerve cells to surface roughness have been studied on various substrates, such as porous silicon, [3] thin titanium nitride films, [4] carbon nanotubes, [5] topographically molded poly(dimethylsiloxane), [6,7] silicon pillar arrays, [8] gallium phosphide nanowires, [9] aligned nanofiber arrays, [10] and silicon nanowires. [11] Previous studies showed that nerve cells exhibit enhanced attachment and viability [3][4][5][6] as well as the axonal guidance effect [7-10, 12, 13] on rough surfaces, as opposed to topographically flat surfaces.…”
mentioning
confidence: 99%
“…Patterning dissociated mammalian neurons and characterizing their functional connections have been one of the main approaches for these studies [6,7]. Recently, as the development of methods for microfludics [8][9][10][11][12][13][14][15][16] and cell patterning [17][18][19][20][21][22][23][24], experimental evidence revealed that extracellular signals play important roles in the guidance of neurites [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The cells are highly influenced by the properties of the growth substrates. [1][2][3][4] It has been recognized that structured surfaces are more favorable for axonal growth than smooth ones. 5,6 Recent studies demonstrate that topographic cues -even at the nanoscale -influence neuronal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 0.3 ml of 25 wt% aqueous ammonia solution was added to the reaction slurry, and the sonication continued for the following 25 minutes. Fabrication of substrates coated with gold nanoparticles The 0.050 g of haucl 4 (17 wt% solution in hcl) was dissolved in 50 ml of double-distilled water. a glass slide was positioned in a sonication cell containing a water-ethanol solution, and sonication started.…”
mentioning
confidence: 99%